Factors That Influence of Mental Disorder Among Teenager - Raudhatul Mumtahanah; Popon Siti Wulandari; Wahyunengsih Wahyunengsih (Universitas Islam Negeri Sumatera Utara Medan, 2022)
The purpose of this study was to determine what factors trigger mental disorders experienced by adolescents. The object of this study amounted to 186 parents who have children at the junior high school level and senior high school level. Data was taken based on a questionnaire. The results showed that each teen has different causes of mental disorders. The causative factor can be influenced by the home environment and school environment, both from parents and peers.